PENGARUH PROFITABILITAS, GCG, DAN LEVERAGE TERHADAP AGRESIF PAJAK PADA PERUSAHAN LQ45 YANG TERDAFTAR DI BEI PADA TAHUN 2019-2020 - Zulfa Afifah; Anik Malikah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to prove how the influence of Profitability, Good Corporate Governance, and Leverage on Tax Aggressiveness in LQ45 companies listed on the IDX in 2019-2020. The sample in this study were companies listed on LQ45 in 2019-2020 which were published through the official website of the Indonesia Stock Exchange, namely www.idx.co.id The sampling in this study used the purposive sampling method while the data analysis technique used in this study was a test. descriptive statistics, normality test, classical assumption test, multiple linear regression analysis, and hypothesis testing with a significant level (α) of 0.005. The results of this study indicate that independent commissioners, audit committee, and managerial ownership have no effect on tax aggressiveness. Meanwhile, profitability and leverage have a significant effect on tax aggressiveness.Keywords: profitability, independent commissioners, audit committees, managerial ownership, and leverage and tax aggressiveness